Clinical significance of fatal laryngeal stridor in fatal familial insomnia. Issue 4 (16th April 2019) - Fukuoka, Takuya; Kawasaki, Hitoshi; Nakazato, Yoshihiko; Takahashi, Kazushi; Ikeda, Kei; Furuya, Tomotsugu; Miyake, Akifumi; Mitsufuji, Takashi; Ito, Yasuo; Araki, Nobuo; Yamamoto, Toshimasa
Abstract: Background: Fatal familial insomnia (FFI) is characterized by numerous signs and symptoms, including progressive insomnia; dysautonomia and endocrine disturbances; and motor disturbances such as myoclonus, ataxia, parkinsonism, spasticity, dysarthria, and dysphagia. Mental health and behavioral changes include impaired concentration and memory, as well as confusion and hallucinations. FFI patients frequently die due to secondary infections and sudden insomnia‐induced death. To date, laryngeal stridor has not been fully investigated in FFI patients. Aim: This study aims to clarify the mechanism of laryngeal stridor in patients with FFI. Methods: We retrospectively analyzed the clinical records of two FFI patients. Results: Two men (age: 58 and 61 years) were diagnosed with FFI. They showed laryngeal stridor, swallowing dysfunction, and respiratory failure. They required mechanical ventilation, followed by a tracheostomy. Conclusion: Laryngeal stridor in FFI was not previously investigated in detail. If laryngeal stridor occurs in awake FFI patients, emergency tracheostomy should be performed.